Anticipating Chinese reactions to U.S. posture enhancements - Gunness, Kristen (RAND Corporation, 2022)
The dramatic increase in Chinese power and military capabilities over the past two decades has prompted numerous calls for U.S. policymakers, and the U.S. Department of Defense (DoD) in particular, to reevaluate their approach to the Indo-Pacific region, including changes to U.S. military posture. This report provides a framework for assessing likely Chinese reactions to planned or proposed posture enhancements in the Indo-Pacific region. The authors demonstrate how U.S. Army and other military planners can apply the framework to assess an enhancement's likely deterrent value and whether it may induce aggressive People's Republic of China (PRC) responses. Although the framework cannot provide definitive predictions regarding specific Chinese reactions, it helps to ensure consideration of the factors and characteristics most directly linked with Chinese perceptions and behavior. The framework contains three main components. First, it identifies the key factors that appear to drive Chinese thinking and reactions. Second, it assesses how the characteristics of U.S. posture enhancements-their location, the U.S. allies or partners involved, their military capabilities, and the public profile or messaging that accompanies them-may affect Chinese reactions through each key factor. Third, the framework provides a typology of potential Chinese reactions, organized by their level of intensity. The authors apply the framework to three hypothetical U.S. posture enhancements to demonstrate its use and offer insights and recommendations for DoD and Army planners and policymakers
Keywords: Militärpolitik; USA; Indopazifik; China; World politics / 21st century / Forecasting; China / Foreign relations / United States / 21st century; China / Military policy / 21st century; United States / Foreign relations / China / 21st century; United States / Military policy / 21st century; Diplomatic relations; Military policy; World politics / Forecasting; United States; 2000-2099